Takdir Dalam Genggaman: Memahami dan Menerima Ketentuan Ilahi - Hariroh, Syarifah; Muhammad Alif (STAIN MAJENE, 2025)
Destiny is a decree of Allah SWT for everything that happens in the universe, this destiny has existed since before the creation of the universe and this decree cannot be changed and applies absolutely to all parties. This study examines the concept of destiny from the perspective of hadith by examining how to understand destiny. The aim is to find out what hadiths are related to destiny in order to understand the messages contained in the hadith. By using this type of qualitative research with the thematic method of hadith and grounded theory which means collecting data, data according to the truth and collecting hadiths based on themes related to destiny. Based on the results of this study, it shows that there are many hadiths related to destiny. Among them, Saḥiḥ Muslim No. 4797, the meaning of this hadith is that Allah SWT has determined destiny five thousand years before the creation of the heavens and the earth. Second, Sunan At-Tirmiżī No. 2082 Allah SWT has determined the destiny of fifty thousand before the creation of the heavens and the earth and the Throne of Allah is above the water. Third Ṣaḥiḥ Bukhāri No.3208 regarding Allah sending angels for 4 things, namely his deeds, his sustenance, his death, his misery or happiness. The author categorizes several categories, namely: talking about Allah's view of destiny, destiny that speaks about humans.